Impact of Work Facilities on Employee Performance at PT. Kopojeka Daya Indonesia - Faidal, Rida Ahmad; Najibullah, Najibullah; Sabaruddin, Rasfiuddin (Transforma Jurnal Manajemen, 2023)
Work facilities play an important role in improving employee performance. This study aims to analyze the effect of work facilities on employee performance at PT Kopojeka Daya Indonesia. This study uses a quantitative approach with a simple linear regression method. The population in this study were all employees of PT Kopojeka Daya Indonesia, with a sample of 73 respondents taken using saturated sampling techniques. Data collection was carried out through questionnaires and interviews. The results of the analysis showed that there was a positive relationship between work facilities and employee performance with a correlation coefficient value of 0.503. The results of the determination test (R²) showed that work facilities contributed 30.2% to employee performance, while the rest was influenced by other factors. The t-test showed that work facilities had a significant effect on employee performance with a t_count value of 5.539 and a significance of 0.000 <0.05. Thus, good work facilities can improve employee performance at PT Kopojeka Daya Indonesia.